2018
DOI: 10.1017/s0265051717000250
|View full text |Cite
|
Sign up to set email alerts
|

School-based integrated curriculum: An integrated music approach in one Hong Kong kindergarten

Abstract: The implementation of a school-based integrated curriculum enables schools to plan a balanced, flexible and coherent curriculum in order to reduce subject specification, especially in kindergartens. Despite kindergarten teachers in Hong Kong Special Administrative Region (SAR) being encouraged to integrate music content across subject areas, these boundaries still exist and prove challenging. This instrumental case study shows how one kindergarten teacher attempted to integrate other subjects into the music cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
3
16
0
6
Order By: Relevance
“…These misalignments between what national curriculum frameworks in Singapore and Hong Kong propose, on one hand, and what their respective societies actually demand, on the other hand, trigger important challenges for the various stakeholders involved in kindergarten education (Chan, 2016; Lau and Grieshaber, 2018; Lim-Ratnam, 2013). For example, while teacher educators are expected to teach about globally accepted ECE theories and practices in their courses, many often complain that such training will not be applicable by students in local settings.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…These misalignments between what national curriculum frameworks in Singapore and Hong Kong propose, on one hand, and what their respective societies actually demand, on the other hand, trigger important challenges for the various stakeholders involved in kindergarten education (Chan, 2016; Lau and Grieshaber, 2018; Lim-Ratnam, 2013). For example, while teacher educators are expected to teach about globally accepted ECE theories and practices in their courses, many often complain that such training will not be applicable by students in local settings.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In recent studies, many scholars have accepted that the NEL and the Guide should be implemented accurately in kindergartens, hence adopting Western ECE notions without critically assessing their applicability and suitability in the local context, and have emphatically argued that more efforts should be made to better train kindergarten teachers and educate parents so that Western-based pedagogies become the norm (e.g. Bautista et al., 2016; Chan, 2016; Lau and Grieshaber, 2018; Leung, 2020; Lim-Ratnam, 2013). In contrast, our argument in this article is that efforts should be also made to revise the curriculum frameworks themselves, as discussed in the following section.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Research endeavors were made to explore the links between practitioners' career development and SBCD (e.g., Lee, 2017;Loh & Tam, 2017). Findings suggest the structural and socio-cultural challenges that practitioners encountered in schoolbased curriculum decision-making (e.g., Lau & Grieshaber, 2018;Lee et al, 2018;Yang & Li, 2018). There are also a few studies that document how nurturing reflective and collaborative practitioners could counteract the impacts of centralized curriculum planning (e.g., Yuen et al, 2018;Zhan et al, 2016).…”
mentioning
confidence: 99%
“…Methodologically, the case study approach was predominantly used to study various aspects of SBCD in Hong Kong, such as leadership (e.g., Law et al, 2010;Lee & Dimmocks, 1998), challenges and tensions faced by practitioners (e.g., Lee, et al, 2018), and SBCD as a reflective practice (e.g., Yuen et al, 2018). Interviews prevailed as data collection methods (e.g., Lai et al, 2014;Loh & Tam, 2017;Yuen et al, 2018;Zhan et al, 2016) whilst a few applied observation (e.g., Lau & Grieshaber, 2018;Yang & Li, 2018). For example, Zhan et al (2016) used in-depth interviews with document analysis to study how teachers implemented Liberal Studies and found that teachers tended to adapt their teaching approaches and teaching materials instead of content and assessment.…”
mentioning
confidence: 99%